2023
DOI: 10.1111/jcms.13522
|View full text |Cite
|
Sign up to set email alerts
|

Supranational Entrepreneurship Through the Administrative Backdoor: The Commission, the Green Deal and the CAP 2023–2027

Abstract: The Green Deal, the European Commission's current economic and environmental flagship initiative, demands policy change in many fields. One of them is the Common Agricultural Policy (CAP), which has a history of complex and controversial reforms. This raises a classic question of EU studies: To what extent and under what conditions can the Commission act as a policy entrepreneur? Analysing its efforts to align the latest CAP reform with the Green Deal, this article shows that, whilst struggling to make an impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…When assessing meta‐governance and the steering of policies through objectives, treating the European Commission as a unitary actors is plausible especially in light of the strategic function of its leadership level (Kassim et al, 2017). Such a view is less feasible when analysing policy instruments that translate EU governance architectures into concrete measures and thus are at the responsibility of different sub‐units of the European Commission bureaucracy (e.g., Becker, 2023, p. 3; Rauh, 2021). Additionally, while we identify the European Commission as a focal entrepreneur for norm reconfiguration, the results of this exploration would clearly also benefit from an integrative reading with similar research on other EU institutions' agency during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing meta‐governance and the steering of policies through objectives, treating the European Commission as a unitary actors is plausible especially in light of the strategic function of its leadership level (Kassim et al, 2017). Such a view is less feasible when analysing policy instruments that translate EU governance architectures into concrete measures and thus are at the responsibility of different sub‐units of the European Commission bureaucracy (e.g., Becker, 2023, p. 3; Rauh, 2021). Additionally, while we identify the European Commission as a focal entrepreneur for norm reconfiguration, the results of this exploration would clearly also benefit from an integrative reading with similar research on other EU institutions' agency during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The steering of EU policies along overarching objectives goes even further back in time and ever since has also involved the European Commission's entrepreneurship. As such, research on EU structural funding illustrates how the European Commission has continuously shifted its tasks from funding implementation towards the management of the funds' objectives (Becker, 2023; Heinelt & Malek, 2002). Next to designing EU governance architectures, research shows that the European Commission has also made use of governance architectures to expand its role in certain policy areas, notably also in one of the two assessed areas at hand, namely higher education (Keeling, 2006).…”
Section: Theoretical Integration: Norms and Crises In Eu Governancementioning
confidence: 99%
“…Since the debate in the 1990s, only three studies of public sector policy entrepreneurs have addressed aspects of democracy, focusing on accountability of individual agency employees in the US state government [69], the legitimacy of Swedish local authorities [70], and the accountability of the European Central Bank [65] as policy entrepreneurs. Some scholars have admitted that policy entrepreneurs can have implications regarding trust, legitimacy, and accountability [45,[71][72][73][74], but they did not analyse it. This critical perspective is not included in the future research agendas suggested on policy entrepreneurs in general [40], and on policy entrepreneurs in climate governance [42,46,75].…”
Section: A Call For Critical Research On Policy Entrepreneursmentioning
confidence: 99%
“…Policy entrepreneurship can be deployed by actors in and out of government at different levels, and in different domains, if they are "persistent and skilled actors who launch original ideas, create new alliances, work efficiently or otherwise seek to 'punch above their weight'" [46] (p. 1344) [75]. For instance, the current president of the European Commission, Ursula von der Leyen, and former EU commissioner Frans Timmermans have been described as policy entrepreneurs for launching the 'European Green Deal' (EGD) in 2019 [74,85], and the EU High Representative for Foreign Affairs and Security Policy, Federica Mogherini, acted as a policy entrepreneur and pushed for policy change in the EU's foreign and security policy [86,87]. In all, acting as a policy entrepreneur depends on a "set of behaviours in the policy process, rather than a permanent characteristic of a particular individual or role" [88] (p. 78).…”
Section: Defining Policy Entrepreneursmentioning
confidence: 99%
“…Equally important to mention is that the bioeconomy can create 400,000 new green jobs by 2035, especially in rural and coastal areas, underpinned by regional and national strategies, with funding of up to €250 million for green projects through the European Circular Bioeconomy Fund. Investments in agriculture, aquaculture, fisheries, forestry sectors, biochemistry, biomaterials, energy efficiency in housing and use of bio-based insulation materials etc., are a great opportunity, but in order to make them a success, they need to be strongly anchored in the constitutional framework of the EU legal order, in particular, in the concepts of solidarity, sustainable development and high level of environmental protection [21][22][23].…”
Section: Bioeconomy Strategymentioning
confidence: 99%